Making mutual learning tangible: Mixed-method Delphi as a tool for measuring the convergence of participants’ reciprocal understanding in transdisciplinary processes - Pfendtner-Heise, Jannis; Ackerschott, Adriana; Schwenck, Christoph; Lang, Daniel J.; Wehrden, Henrik von (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
This paper proposes an approach to capture mutual learning within transdisciplinary research to develop future-oriented sustainability solutions to land use conflicts. While quality criteria for transdisciplinary research projects are increasingly discussed, there is still ample methodological potential to enable and better understand mutual learning as a key component of transdisciplinarity. Changes in the specific developments of perceptions of the participants are difficult to be tamed and tracked. To address this shortcoming we propose to apply the Delphi method for longitudinal tracking of mutual learning within transdisciplinary research. We present the application of the methodological approach as part of a transdisciplinary project on sustainable land use in the district of Lüneburg (Lower-Saxony, Germany). Evaluation of semi-structured interviews with seven participants translated into a three-round Delphi survey. A concluding round of semi-structured interviews was performed to validate and deepen the findings. The results showcase that the Delphi method can facilitate the operationalization of the convergence of understandings as a relevant outcome of mutual learning within transdisciplinary projects.
Keywords: Delphi; Mutual Learning; Transdisciplinary Science; Sustainability Transition; Land-Use